On the nature of intermittency in a turbulent von Kármán flow. (5th March 2021) - Faller, H.; Geneste, D.; Chaabo, T.; Cheminet, A.; Valori, V.; Ostovan, Y.; Cappanera, L.; Cuvier, Ch.; Daviaud, F.; Foucaut, J.-M.; Guermond, J.-L.; Laval, J.-Ph.; et al.
Abstract: Abstract : We have conducted an extensive study of the scaling properties of small scale turbulence using both numerical and experimental data of a flow in the same von Kármán geometry. We have computed the wavelet structure functions, and the structure functions of the vortical part of the flow and of the local energy transfers. We find that the latter obey a generalized extended scaling, similar to that already observed for the wavelet structure functions. We compute the multi-fractal spectra of all the structure functions and show that they all coincide with each other, providing a local refined hypothesis. We find that both areas of strong vorticity and strong local energy transfer are highly intermittent and are correlated. For most cases, the location of local maximum of the energy transfer is shifted with respect to the location of local maximum of the vorticity. We, however, observe a much stronger correlation between vorticity and local energy transfer in the shear layer, that may be an indication of a self-similar quasi-singular structure that may dominate the scaling properties of large order structure functions.